Analisis Jaringan 3-Dimensi Untuk Penentuan Rute Evakuasi di Gedung Bertingkat - Taufik Hery Purwanto (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Accessibility of evacuation routes in the multi-storey building is an important thing to notice. The number of floors and rooms in multi-storey buildings which are too many often makes the building users have difficulty, especially for users who do not know the ins and outs of the building well. Not only the difficulty in finding evacuation routes to exit the building quickly in emergency times, but also to find a certain room during normal times. Nowadays, the Network Analysis capabilities in Geographic Information System (GIS) have become more reliable, even able to accommodate 3 Dimensional aspect (3D) which is often known as 3D Network Analysis. Therefore, this research intends to apply 3D Network Analysis for developing the navigation and evacuation management system in the KLMB (Klinik Lingkungan dan Mitigasi Bencana) Building Faculty of Geography UGM which has 6 floors. Generally, the implementation of this research can be divided into 4 main stages, namely Data Collection Stage, 3D Network Dataset Preparation Stage, 3D Network Analysis Implementation Stage, and Test & Evaluation Stage. Through application of the 3D Network Analysis, this research successfully obtained a navigation and evacuation management system in the ArcScene (ArcGIS) software environment which is quite effective and easy to use to help navigation and determination of the fastest evacuation route in the KLMB building. This system can also be used to help the evacuation simulation as a form of disaster mitigation in the KLMB Building.